ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI PRODUK PRIVATE LABEL - Adi, Bramasto; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2017)
This study aims to investigate factors influencing purchase intention of private label product. The factors, such as price perception, quality perception, risk perception, intrinsic cues, extrinsic cues, and familiarity, were examined to find out which factors played significant role on purchase intention of private label product. The examination was also looking for the differences of factors influence on both groups of gender which were male and female.Using probability sampling method, the datas were raised by spreading questionnaires to 120 young adults in Semarang who knew the information about private label product. Collected data were analysed with IBM SPSS 21 for windows using some methods such as validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, ANOVA, R Square, and T test.The findings of study indicate some factors such as price perception, quality perception, and familiarity significantly influence purchase intention of private label product. Also, the findings explain that male likely take a risk than female.